Electronic Authentication of E-commerce Contracts - Ibrahim, Shady Ramadan (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed at explaining the electronic authentication from a technical and legal point of view, and to explain the authentication mechanism represented in encryption and its types, and to clarify the role of electronic certification in electronic transaction. We also clarified the role of documentation in electronic editors and the scope of electronic documentation, as well as how to authenticate in the field of e-mail, and the role of trustworthy third parties in the process. The study also clarified the method and mechanism of electronic documentation in the field of electronic preservation services. Based on the nature of the research, a comparative approach was followed by presenting the position of more than one local and international legislation besides conducting an analytical study. The researcher also used the analytical method by addressing each section after analyzing it through jurisprudential opinions and national laws where the descriptive method issued to clarify some concepts that include a careful analysis of information and facts about the subject of study.After presenting the research material, several results were reached, including: that electronic authentication services are the legal means to send confidence and secure online dealings. Based on the results, the researcher made a set of recommendations, including the recommendation to issue a comprehensive legislation that regulates the role played by trustworthy third parties in terms of electronic signature, recommended e-mail, and electronic preservation.
Keywords: electronic commerce; electronic signature; electronic documentation; electronic writing; encryption